Measuring pro-poor growth with non-income indicators - Melanie Grosse; Kenneth Harttgen; Stephan Klasen (Georg-August-Universität Göttingen, Ibero-America Institute for Economic Research (IAI), 2005)
In order to track progress on MDG1 and explicitly link growth, inequality, and poverty reduction, several measures of 'pro-poor growth' have been proposed in the literature and used in applied academic and policy work. These measures, particularly the ones derived from the growth incidence curve, allow a much more detailed assessment of the distributional impact of growth and its link to poverty reduction. At the same time, this toolbox has been developed and to date only applied for tracking progress in reducing the income dimension of poverty. There are no corresponding measures for tracking progress on non-income dimensions of poverty, and thus progress on MDGs 2-6. In this paper, we propose to extend the approach of pro-poor growth measurement to non-income dimensions of poverty (particularly health and education). We show theoretically and illustrate with data from Bolivia empirically that it is possible to extend this pro-poor growth toolbox to non-income dimensions and show that it generates new insights. In particular, it allows a much more detailed assessment of progress towards MDGs 2-6 by focusing on the distribution of progress, rather than simply focusing on mean progress. Moreover, this extension allows the assessment of the linkage between progress in income and non-income dimensions of poverty which is an important extension to traditional incidence analysis and furthermore allows an explicit assessment of the linkage between progress in MDG1 and MDGs 2-6.
Keywords: D30; I30; O10; O12; 330